2021
DOI: 10.11124/jbies-20-00297
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of learning, development, and preparedness for clinical practice among undergraduate paramedicine students, graduate/intern paramedics, and their preceptors: a qualitative systematic review

Abstract: The educational landscape for paramedicine has evolved considerably since the introduction of the first paramedicine bachelor degree. This systematic review aims to identify and explore the barriers to and facilitators of learning and preparedness for clinical practice among undergraduate paramedicine studnets, graduate/intern paramedics and their preceptors. This review was undertaken in accordance with the JBI Reviewer's Manual. The full methods will be published in the final review report. Results:Twenty si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Standardised delivery of theory, skills and maternity placements across HEIs would support a reduction in variation. Hanna et al (2021) explored experiences of learning, development and preparedness for clinical practice among undergraduate paramedicine students via a systematic review, and identified similar themes. The review highlighted a need for more effective communication between universities and integrated systems to address challenges in paramedicine education, supporting a collaborative identification of educational models that best facilitate learning, development and preparedness for clinical practice ( Hanna et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardised delivery of theory, skills and maternity placements across HEIs would support a reduction in variation. Hanna et al (2021) explored experiences of learning, development and preparedness for clinical practice among undergraduate paramedicine students via a systematic review, and identified similar themes. The review highlighted a need for more effective communication between universities and integrated systems to address challenges in paramedicine education, supporting a collaborative identification of educational models that best facilitate learning, development and preparedness for clinical practice ( Hanna et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Hanna et al (2021) explored experiences of learning, development and preparedness for clinical practice among undergraduate paramedicine students via a systematic review, and identified similar themes. The review highlighted a need for more effective communication between universities and integrated systems to address challenges in paramedicine education, supporting a collaborative identification of educational models that best facilitate learning, development and preparedness for clinical practice ( Hanna et al, 2021 ). Despite a focus on pre-registration training and education, a gap exists in understanding of the level, depth and content of training provided to all staff who provide pre-hospital maternity and newborn care, including emergency medical technicians, community first responders and call takers.…”
Section: Discussionmentioning
confidence: 99%
“…Paramedics routinely work in limited resource and chaotic environments and many decisions regarding, in some instances, quite complex interventions, need to be made quickly and under high stress [ 22 ]. To this end the development of student paramedics to be clinically prepared at the end of their formal academic education continues to be a challenge for educators [ 23 ]. Results from this study have provided valuable insight into the validity of the SCT in paramedicine and the variance between expert and novice paramedics clinical reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…19 Another review explored preceptors and the experiences of paramedics. 20 The nursing workforce is in a state of global crisis, and this review will include the voices of prelicensure nurses in their final weeks of clinical preparation, and will magnify their preceptorship experiences, specifically focusing on the immediate clinical experience that takes place in their pre-transition to the nursing profession. 12 Baccalaureate nursing students' most recent and immediate clinical preceptorship is the focus of this review.…”
Section: Introductionmentioning
confidence: 99%